A systematic literature review of observational studies of the bilateral association between diabetes and migraine. Issue 3 (May 2021) - Hosseinpour, Marjan; Maleki, Farzad; Khoramdad, Maliheh; Sullman, Mark J.M.; Nejadghaderi, Seyed Aria; Kolahi, Ali-Asghar; Safiri, Saeid
Abstract: Background and aim: To conduct a systematic literature review and synthesize data from all epidemiological studies investigating the association between diabetes and migraine in adults. Method and material: Electronic databases, including Web of Science, PubMed and Scopus in addition to Google Scholar search engine were systematically searched up to Jun 2020 to identify studies reporting the diabetes-migraine association. Results: A total of 15 studies were selected which were published from 2012 to 2019. Five out of 15 studies assessed the presence of migraine in diabetic subjects, while nine studies assessed the presence of diabetes in migraine subjects. The cohort study reported a hazard ratio for diabetes of 1.06 (95% confidence interval (CI): 0.91–1.24) for women with migraine with aura, 1.01 (95% CI: 0.89–1.16) for women without aura, and 1.13 (95% CI: 0.98–1.3) for women with a migraine history, compared with women with no history of migraine. Due to the high degree of heterogeneity, and the lack of statistical estimates of the association in several of the reviewed studies, meta-analysis of the available data was not possible. Conclusion: This study is the first review to examine the association between diabetes and migraine. Further longitudinal studies are required to clarify the migraine-diabetes association. There is also a clear need for more studies with larger sample sizes and similar methodologies in order to provide necessary information to conduct a meta-analysis. Highlights: All studies were published in 2012–2019, so this is a new research field. The diabetes-migraine association has been reported as bidirectional. More confounder and interaction variables need to be considered and evaluated.